TAMPILAN PRODUKSI SUSU SAPI PERAH YANG MENDAPAT PERBAIKAN MANAJEMAN PEMELIHARAAN - Budi Utomo; Miranti Dian Pertiwi (Caraka Tani: Journal of Sustainable Agriculture, 2010)
A study was addressed to evaluate the effect of rearing management improvement particularly for feed and housing management on milk production of dairy cattle. The investigation was performed at Kembang Village, Ampel Sub-District of Boyolali District, a location for Prima Tani implementation, involved the participation of 8 people of farmer group members. A group of four cattle fed the traditional diet, whereas the remaining four were offered the introduced diet containing elephant grass + commercial concentrate + cassava tuber. Measurements were made for feed intake, milk production, and milk density. Results showed that milk production of dairy cattle under the improved management was higher (P<0.05) than that under the traditional one (7.08+ 0.31 versus 4.59 + 0.39 l/head/d). It was determined that the average of dry matter intake of the cattle under the traditional rearing management was 7.79 + 0.61 kg/head/d, while the cattle received the introduced diet consumed 8.29 + 0.61 kg dry matter/head/d. However, the average milk density of the cattle under the traditional rearing management (1.0253) was similar to that of cattle under the improved management (1.0271). The conclusion was that improvement of rearing management increased the amount of milk produced by dairy cattle.